4-coils magnetic resonance coupling wireless power transfer with varying rotational angle - Tan S.Y.; Lee H.J.; Ker P.J. (Institution of Engineering and Technology, 2023)
Efficiency; Electric fields; Energy transfer; Magnetic couplings; Magnetic resonance; Magnetism; Comparative analysis; Electric field and magnetic field; Magnetic resonance couplings; Magnetic resonant; Performance parameters; Rotational angle; Wireless power transfer; Wireless power transfer (WPT); Inductive power transmission